Pengaruh Gaya Kepemimpinan Transformasional, Kompensasi, Dan Budaya Organisasi Terhadap Produktivitas Kerja Karyawan (Studi Pada PT. Berlian Multi Servindo di Kabupaten Kotawaringin Barat) - Ibnu Zakaria; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract There are many factors that can lead to consistently lower productivity and less than optimal performance, including a transformational leadership style and an organizational culture that is not implemented properly. This study uses quantitative methods using primary and secondary data. 42 employees made up the study’s sample. While the sample of this study is all members of the population. The technique of taking samples using the total sampling method. The conclusions that can be derived from the analysis and discussion’s findings are as follows. (1) According to the F test results it is concluded that Transformational Leadership Style, Compensation, and Organizational Culture have a simultaneous influence on Employee Work Productivity, (2) The results obtained in this study can be concluded that partially Transformational Leadership Style has a significant positive effect on Work Productivity Employees, (3) The results obtained in this study can be concluded that partially Compensation has a significant positive effect on Employee Productivity, (4) The results obtained in this study can be concluded that partially Organizational Culture has a significant positive effect on Employee Productivity. Keywords: Transformational Leadership Style, Compensation, Organizational Culture, Employee Productivy